Role of Guanylyl Cyclase Activation via Thiamine in Suppressing Chemically-induced Writhing in Mouse - Abacioğlu, Nurettin; Demir, Sema; Çakici, İclal; Tunçtan, Bahar; Kanzik, İlker (Arzneimittelforschung, 2000)
The possible role of L-arginine/nitric oxide (L-arginine/NO) pathway in the antinociceptive activity of thiamine (vitamin B1 in p-benzoquinone-induced mouse writhing model was investigated. Thiamine (ED50, 0.11 mg/kg), L-arginine (50 mg/kg), NG-nitro-L-arginine methyl ester (L-NAME, 75 mg/kg) and morphine (ED50: 0.13 mg/kg) displayed antinociceptions following s.c.aministrations (52.4 ± 5.5%, 36.8 ± 7.7%, 27.8 ± 11.1%, 66.1 ± 3.5%, respectively). However, methylene blue (MB, 40 mg/kg, s.c.) produced a nociception (-32.1 ± 9.9%). Coadministration of B1 with L-arginine did not significantly change L-arginine-induced antino-ciception (48.9 ± 3.7%). Cotreatment of thiamine with L-NAME and MB significantly increased the L-NAME-induced antinociception (53.9 ± 3.9%) and reversed the MB-induced nociception to antinociception (46.0 ± 4.2%). L-Arginine and L-NAME-induced antinociceptions were significantly increased (55.9 ± 3.9% and 61.1 ± 5.0%, respectively) by morphine. MB-induced nociception significantly reversed to antinociception by the concomitant administration of morphine (41.6 ± 8.9%). Thiamine and morphine coadministration displayed antinociception (46.0 ±4.2%). The present results suggest that thiamine could produce antinociception by the activation of guanylyl cyclase mediated by cyclic guanosine monophosphate (cGMP) that may trigger the possible involvement of central and/or peripheral L-arginine/ NO/cGMP pathway.
Keywords: L-Arginine/NO/cGMP; Guanylyl cyclase, antinociception, mouse; Thiamine